Umowy przewozu i spedycji w realizacji przewozów multimodalnych (kombinowanych) przy użyciu kontenerów: [Transport and forwarding agreements versus multimodal (combined) transport by containers] (Studia Prawnicze / The Legal Studies, 2023)
The article aims at the juridical assessment to what degree the traditional civil and legal instruments (transport and forwarding agreements) relating to multimodal (combined) transport by containers are availed of.In the article the premises have been pointed to which, under the regulations in force, account for a more frequent use of containers in dispatching various consignments. The author has argued that containerization accounts for the emergence of new organizational forms of the transport of commodities, first of all the so called multimodal transport. The technological and organizational transformations in transport are a natural and efficient stimulous for transport and forwarding enterprises to expand their present, traditional scope of tasks. Therefore the traditional range of their activities as transport and forwarding agents, availing of containers in multimodal dispatches, has undergone essential transformations. They either organize container transport or correlate combined dispatches, having been furnished with an increased scope of tasks.Although new organizational forms of transport integrate the process of transport, the analysed civil and legal measures in force- are applicable only in the traditional transport. Since the efficiency of the multimodal (combined) transport is conditioned by the enactment of adequate legal measures, the author postulates The article aims at the juridical assessment to what degree the traditional civil and legal instruments (transport and forwarding agreements) relating to multimodal (combined) transport by containers are availed of.In the article the premises have been pointed to which, under the regulations in force, account for a more frequent use of containers in dispatching various consignments. The author has argued that containerization accounts for the emergence of new organizational forms of the transport of commodities, first of all the so called multimodal transport. The technological and organizational transformations in transport are a natural and efficient stimulous for transport and forwarding enterprises to expand their present, traditional scope of tasks. Therefore the traditional range of their activities as transport and forwarding agents, availing of containers in multimodal dispatches, has undergone essential transformations. They either organize container transport or correlate combined dispatches, having been furnished with an increased scope of tasks.Although new organizational forms of transport integrate the process of transport, the analysed civil and legal measures in force- are applicable only in the traditional transport. Since the efficiency of the multimodal (combined) transport is conditioned by the enactment of adequate legal measures, the author postulates that they should be modelled on the traditional solutions, but opposes the attempts to avail of the existing transport and forwarding agreements to this end.that they should be modelled on the traditional solutions, but opposes the attempts to avail of the existing transport and forwarding agreements to this end.